Evidence that supports the prescription of low-carbohydrate high-fat diets: a narrative review. Issue 2 (4th January 2017) - Noakes, Timothy David; Windt, Johann
Abstract : Low-carbohydrate high-fat (LCHF) diets are a highly contentious current topic in nutrition. This narrative review aims to provide clinicians with a broad overview of the effects of LCHF diets on body weight, glycaemic control and cardiovascular risk factors while addressing some common concerns and misconceptions. Blood total cholesterol and LDL-cholesterol concentrations show a variable, highly individual response to LCHF diets, and should be monitored in patients adhering to this diet. In contrast, available evidence from clinical and preclinical studies indicates that LCHF diets consistently improve all other markers of cardiovascular risk—lowering elevated blood glucose, insulin, triglyceride, ApoB and saturated fat (especially palmitoleic acid) concentrations, reducing small dense LDL particle numbers, glycated haemoglobin (HbA1c ) levels, blood pressure and body weight while increasing low HDL-cholesterol concentrations and reversing non-alcoholic fatty liver disease (NAFLD). This particular combination of favourable modifications to all these risk factors is a benefit unique to LCHF diets. These effects are likely due in part to reduced hunger and decreased ad libitum calorie intake common to low-carbohydrate diets, allied to a reduction in hyperinsulinaemia, and reversal of NAFLD. Although LCHF diets may not be suitable for everyone, available evidence shows this eating plan to be a safe and efficacious dietary option to be considered. LCHF diets may also be particularly beneficial in patients with atherogenic dyslipidaemia, insulin resistance, and the frequently associated NAFLD.